THE DISCRETIONARY POWER OF LEGISLATOR IN THE TAX FIELD"COMPARATIVE STUDY" - Akram Hadi Mohessin, Zaid Ajmi Bisheet Al-Rikabi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The paper gives a comprehensive account ofthe discretionary power of the tax legislator that is one of the essential topics in the study of public finance and the basis for tax administration following the principle of tax legality. The legislative authority in democratic countries has been entrusted with the legislative authority, for many considerations, some of which are legal and others mentally or philosophically.The elected legislative authority in its entirety represents the will of the sovereign people.Therefore; the attribution of the legislative function to the legislative authority embodies the meaning of democracy in its true sense, which means that the people govern themselves by themselves either directly by the people, or indirectly through their representatives in parliament to exercise these powers.The legislative authority in the organic sense is considered a fundamental pillar of democratic political systems, especially as they play a significant role in the field of legislation and oversight. Undoubtedly, the constitution as the highest basic legislation in the state that transcends all existing legal rules in the state within the principle of the graduation of legal rules. It is also a cornerstone in nation-building Legalism based on the principle of the rule of law as one of the main principles for the establishment of the rule of law as long as the constitution is the jurisdiction of each of the three public authorities that have been defined within limits set by them. It is forbidden for every public authority to exercise the powers of another authority, in the application of the principle of separation of powers. Correspondingly, it is stipulated in the laws issued by the legislator that they do not contradict or violate the provisions of the constitution in the application of theprinciple of the graduation of legal rules.